Gambaran Noise pada Pemeriksaan CT-Scan Brain menggunakan Protokol Fast Stroke di Instalasi Radiologi Rumah Sakit Otak DR. DRS. M. Hatta Bukittinggi - Zasneda, Sabriani Suci; Kustoyo, Bambang; Hulu, Yessi Vanni; Saragih, Febby Lolasari (3031-8572, 2022)
Stroke is one of the leading causes of death worldwide, with non-hemorrhagic stroke accounting for 85% of cases. CT-Scan examination is the primary modality for stroke diagnosis. This study aims to determine the examination technique and evaluate noise characteristics in CT-Scan brain examination using fast stroke protocol at Dr. Drs. M. Hatta Brain Hospital, Bukittinggi. This is a qualitative descriptive study conducted from June to July 2023 involving four informants consisting of one doctor and three radiographers. Data were collected through literature review, observation, in-depth interviews, and documentation. The fast stroke protocol uses parameters of 120 kVp, 210 mA, 1.25 mm slice thickness, DFOV 26.9 cm, and total exposure time 4.33 seconds. Results showed that the fast stroke protocol with 1.25 mm slice thickness produces higher noise compared to head routine protocol with 5 mm slice thickness. However, thinner slices provide better detail and can detect smaller lesions, which is crucial for early stroke detection. The head routine protocol produces smoother images with less noise but lower detail. For stroke cases, the fast stroke protocol is more optimal as it can detect smaller lesions in critical areas. Image quality is influenced by slice thickness, where thinner slices increase noise but improve spatial resolution and diagnostic accuracy. It is concluded that the fast stroke protocol is more suitable for stroke cases despite higher noise levels, as the benefits of improved lesion detection outweigh the disadvantages of increased noise